Comparative assessment of changes in the incidence of type I diabetes mellitus in the regions with its high and low incidence - Irada J. Aliyeva (Medičnì Perspektivi, 2021)
The purpose of this study was to determine dynamics of the levels of type I diabetes mellitus (DM) incidence in the regions with its different incidence. Material from the Azerbaijan Republican and Regional Registers of Diabetes Mellitus were used in this study. All cases of newly diagnosed type 1 DM and documented according to the clinical protocol in 2012-2016 were selected. At the first stage of the study, the rates of diabetes were identified in all administrative-territorial entities. Two groups from administrative-territorial entities were formed for further observation: the first group included regions with high (>80) incidence of type 1 DM, the second group included regions with low (<40) incidence of type 1 DM. At the next stages, changes in type 1 DM incidence were studied and a mean chronological incidence over five years (2012-2016) was determined. Morbidity rate in cities and regions of Azerbaijan in 2012 changed within a range from 5.4 to 294.8. The lowest incidence was observed in three districts: 5.4 in Agjabedi, 5.8 in Jalilabad, 6.1 in Masalli. Very high incidence was observed in Shamkir (294.8) and Khachmaz (278.7) districts. Data from Agdash (30.6) and NAR (32.2) were closer to data from the districts with low incidence. Incidence in Shirvan (81.9) and Yexlakh (171.7) districts was high, but lower than in Shamkir and Khachmaz districts. Type 1 DM incidence has significant interregional differences. Interregional differences in type 1 DM incidence do not depend on the age of the population; age-adjusted incidence of type 1 DM is within a range of 5.0-77.4.